Metabolic syndrome in patients with systemic lupus erythematosus - T Y Popkova; D S Novikova; E. V. Gerasimova; E N Alexandrova; A A Novikov; E S Maeh; S. S. Alekberova; E L Nasonov (Научно-практическая ревматология, 2008)
Objective. To characterize metabolic syndrome (M S) in pts wit h systemic lupus erythematosus (SLE) and determine contribution of immune inflammation to the development of MS. Material and methods. 156 females with SLE (mean age 35 years, mean disease duration 99 months) were included. Control group consisted of 69 people of comparable age without rheumatic diseases. MS was diagnosed according to ATP III criteria, \fascular atherosclerotic damage was assessed by carotid sonographic evaluation. Serum cholesterol (CS), triglycerides (TG) and high-density lipoprotein (HDLP) CS concentration was assessed with colorimetric and photometric methods, hs CRP level — with nephelometric immunoassay. Results. MS was revealed in 29 from 154 (19%) pts with SLE and in 5 from 69 (7%) controls (p=0,02). MS components (hypertension, TG elevation and a lipoprotein decrease) in SLE were significantly more frequent than in control group. TG, HDLP CS and CRP levels in SLE were higher than in control. Thickness of carotid intima-media complex did not differ in SLE and control. Frequency of atherosclerotic plaques (15%) and coronary heart disease (14%) in SLE was higher than in control (4% and 2% respectively), p=0,01. Pts with SLE and MS were older, had higher disease activity and maximal glucocorticoid dose during disease period (p<0,05). CRP concentration in SLE with MS was significantly higher. Subclinical signs of atherosclerosis in SLE with MS were more frequent than in SLE without MS (p<0,05). Frequency of clinical signs of atherosclerosis did not differ in these groups. Conclusion. Autoimmune inflammation in SLE plays an important role in the development of MS.